EFFECTIVENESS OF WEB-BASED MEDIA IN INGRAINING POSITIONAL ASTRONOMICAL CONCEPTS - Nuradnan Pramudita, Alma
Interactive simulation can be an adequate study material. For this thesis, a website had been developed, showcasing simulations on positional astronomy. This subject was chosen since it doesn’t require comprehensive understanding of physics. It also provides sense of terrestrial observation of celestial objects. Hopefully, the grasp of this terrestrial sense will lead further to the understanding of the dynamics of astronomical systems. The media for the thesis were developed with p5.js, a library of JavaScript. This framework was chosen for its ability to interact with other web components: HTML and CSS. Compared to other, earlier media, this thesis’ media has the advantage offered by responsive interactive website. Only browser and internet connection are required to run the media. Furthermore, the features of the media had been designed to make possible the making and solving of numeric exercises on positional astronomy. This work aims to measure the effectiveness of the media developed. The utilized methods are testing the hypotheses that there is an increase in grade and calculating the n-gain of pre-test and post-test administered to respondents treated with exposure to the media. The work obtained the result that within 0.05 significance level, there is improvement in grade for all respondents after experiencing the features of the media. Also obtained is the n-gain of 0.272–0.288 in the topic of celestial coordinates and 0.498–0.546 in the topic of Julian date for all respondents.